Pengaruh Pembinaan Disiplin dan Kepuasan Kerja Terhadap Motivasi Kerja Perawat Kontrak di Rumah Sakit XYZ - Latifah; RM Juddy Prabowo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Nurses are an important component besides doctors. As important as doctors, nurses also have a vital role in the treatment and recovery of a disease. This study aims to determine the effect of discipline coaching and job satisfaction on the work motivation of contract nurses at XYZ Hospital. The determination technique is to use the entire population for this study. The data collection methods used in this study are questionnaires, interviews, and documentation. Data analysis used in this study uses multiple linear regression analysis, the coefficient of determination with the SPSS program version 25. Respondents in this study were 98 contract nurses at XYZ Hospital. The results of the study indicate that there is a positive influence of discipline coaching on work motivation and job satisfaction has a positive influence on work motivation. While simultaneously, discipline coaching and job satisfaction have a significant effect on work motivation.